Evaluation of Estradiol and Prolactin Serum Levels "In Premenopausal; and Postmenopausal" Women with ((Breast Cancer)) In Baghdad City - sahan, enas; majed, ali; hassan, ahmed (Iraqi National Journal of Nursing Specialties, 2017)
Objective:To Evaluate of Estradiol and Prolactin hormones levels for Breast Cancer women in Baghdad City. Methodology: The current study was conducted on 60 breast cancer women and 40 apparently healthy subjects to evaluate the levels of estradiol and prolactin "hormones in the serum" of (premenopausal & postmenopausal) breast cancer and healthy controle women. Estradiol and prolactin hormones estimated for all cases by using the IMMULITE 2000 instrument that performs chemiluminescent immunoassays results are calculated for each sample.Data were analysed using SPSS-18.data of two groups was comparison by the student’s t-test. Results: The results showed a non significant""(P>0.05) elevation in the –mean- serum estradiol level of the study (premenopausal &postmenopausal ) group (54.0 + 22.8 pg/ml),(31.6 + 9 pg/ml) respectively compared to that of control (pre& postmenopausal ) group (47.0 + 22.3 pg/ml), (28.4 + 10.7 pg/ml) respectively.while a highly significant (P<0.01) elevation of serum prolactin (30.9 + 18.5 ng/ml) ,(20.9 +15.2 ng/ml) respectively was found in study (premenopausal &postmenopausal ) group compared to healthy control (premenopausal &postmenopausal ) group (11.7 + 10.4" ng/ml"),(8.7 + 5.1 "ng/ml") respectively.The results of this study indicate that the elevation of estradiol and prolactin hormones may implicate these hormones in the aetiology of" breast cancer".. Recommendations: This learn lines recommends emphasizing the necessity of cooperation between the Ministry of Health and the Ministry of Commerce and protecting them from dangerous behavior by providing them with sufficient support and guidance to stay away from the hormonic products and focusing on the extension programs in the protection of the community through educating them with the guidance programs